2016
DOI: 10.1111/jan.13104
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the effectiveness of educational interventions for breastfeeding promotion directed to the woman and her social network

Abstract: Educational interventions were about twice as effective in promoting exclusive breastfeeding at 6 months old. There is a need for further studies applying interventions that address women and their social network from the prenatal period, considering all types of support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
1
11
0
2
Order By: Relevance
“…Despite current efforts to promote breastfeeding worldwide, early weaning is still common and few children receive exclusive breastfeeding by the age of 6 months [29]. A recent review conducted by Bellù [30] found that breastfeeding support is complex and involves individual, structural, and environmental factors.…”
Section: Quantitative Findingsmentioning
confidence: 99%
“…Despite current efforts to promote breastfeeding worldwide, early weaning is still common and few children receive exclusive breastfeeding by the age of 6 months [29]. A recent review conducted by Bellù [30] found that breastfeeding support is complex and involves individual, structural, and environmental factors.…”
Section: Quantitative Findingsmentioning
confidence: 99%
“…Breastfeeding mothers need different types of support that are summarized in the following five forms: informative, emotional, face-to-face, instructional, and self-support [5, 6]. Mothers receive mixed messages about breastfeeding from their social circles, including families and health care providers.…”
Section: Introductionmentioning
confidence: 99%
“…The different types of support provided by the the IBCLCs, and by the peer supporters can fulfil mothers’ needs for information, emotional support, and face-to-face encounters to listen to her concerns, as well as instructional support in the form of practical advice and help. These forms of support can also enhance self-efficacy of the mother, and strengthen her ability to self-support [5].…”
Section: Introductionmentioning
confidence: 99%
“…Such strategies should include the various sectors of society and contribute to increase the duration of breastfeeding (3) . In a meta-analysis study, was verified the efficacy of educational interventions initiated in prenatal care on the prevalence of EBF at 6 months (11) . Maternal self-efficacy is a predictor for breastfeeding that can be modified through educational interventions, which in turn can minimize negative influences of beliefs in maternal self-efficacy for breastfeeding.…”
Section: Introductionmentioning
confidence: 91%